Clinical-radiological and intraoperative discrepancy in massive pneumatosis intestinalis and portomesenteric venous gas in a patient with septic shock (Emergency Care Journal, 2025)
Pneumatosis Intestinalis (PI) and Portomesenteric Venous Gas (PMVG) are radiological findings frequently associated with transmural bowel ischemia and poor prognosis. Their presence usually prompts urgent surgical intervention. A 60-year-old man with a past history of small bowel infarction presented with septic shock, abdominal pain, and elevated serum lactate (3.2 mmol/L). Contrast-enhanced CT demonstrated massive intra- and extrahepatic PMVG with a bubble-like intramural gas pattern in the small bowel. Based on the clinical and imaging findings, emergency laparotomy was performed. Intraoperative exploration revealed bowel distension and mucosal edema with petechial hemorrhage, but no evidence of transmural necrosis. A second-look procedure at 48 hours confirmed the absence of necrosis. This case highlights that even massive PI with PMVG and septic shock may not invariably indicate bowel necrosis. Careful correlation of radiological, laboratory, and clinical findings is essential, and surgical exploration remains mandatory in unstable patients to prevent catastrophic outcomes.
Keywords: Pneumatosis intestinalis; portomesenteric venous gas; intestinal ischemia; septic shock; multidetector computed tomography; exploratory laparotomy; second-look surgery